Innovation process design for servitisation: the digital service innovation case at uvex - Kurtz, Julian; Meyer, Patrick; Lugmair, Nina; Ries, Lena; Roth, Angela (Journal of Enterprise Information Management, 2025)
Purpose: The purpose of this study was to increase knowledge of digital service innovation in servitisation by extending design principles and proposing an innovation process design for smart product-service systems (PSS) development. Furthermore, the study addresses the alignment of multiple stakeholders in the development of smart PSS, thereby bridging the gap between theory and practice. Design/methodology/approach: A qualitative 17-month action design research approach was taken. This study designed an innovation process for smart PSS development. For this, different development streams were synchronised and multiple stakeholder perspectives were integrated. Drawing on the socio-technical systems perspective as theoretical lens, the authors utilised knowledge in the field of digital service innovation and servitisation. In multiple iterations, the authors, together with practitioners, explored how best to synchronise different smart PSS development activities to ensure subsequent operations of the system. Findings: The findings of the longitudinal study conducted with the manufacturing firm uvex propose a hybrid stage-gate innovation process design for smart PSS development. An evaluation with several international academics and practitioners enhances the rigour of the innovative approach. Originality/value: The findings contribute to the literature on digital service innovation and servitisation by applying a rarely used socio-technical perspective to innovation process design for smart PSS development. The longitudinal approach over 17 months in a qualitative action design research setting adds to the knowledge base with novel insights from practitioners’ problems.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Action design research; Digital service innovation; Innovation process design; Product-service systems; Servitization; Socio-technical systems